Investigating the interplay between electricity access and food security: Insights from refugee settlements in Zambia, Malawi, and Uganda - Most, Hedda; Moner-Girona, Magda; Casati, Paola; Llorca, Manuel; Haselip, James; Fumagalli, Elena (Elsevier Inc, 2025)
With increasing displacement trends, low energy access rates in refugee settlements, and the majority of forcibly displaced populations residing in countries experiencing acute food insecurity, the nexus between food security and energy access is increasingly relevant. While the pathways connecting energy access to the four dimensions of food security (availability, access, utilisation, and stability) are well established in the literature, only a few studies empirically provide evidence of the relationship between energy access and food security, particularly in the humanitarian context. Drawing from 926 household-level observations collected via in-person interviews in settlements in Uganda, Malawi, and Zambia, this study contributes new insights on the influence of electricity access on food security in protracted refugee situations. Within the sampled population, 65 % of households experience severe food insecurity while a substantial 76 % majority lacks access to a reliable electricity service. Through a logistic regression analysis, we detect a mitigating effect of electricity access on severe food insecurity, although weakly significant, while controlling for income, gender of the household head, household size, and settlement dummies. The odds of experiencing severe food insecurity are reduced by a factor of 0.7 for households with access to electricity compared to those without access. However, they increase for households located in the most economically disadvantaged settlement. The study highlights the importance of policies that support the right to work and empower female-headed households, as income-generating activities play a mitigating role; in turn, households headed by women are about 1.7 times more likely to experience severe food insecurity compared to those headed by men. More generally, in emphasising the role of reliable energy services in the consumption of safe and nutritious food, this work calls for an integrated humanitarian approach that addresses food security together with long-term, sustainable energy solutions. •Analysis of the pathways connecting energy access and food security•Evidence on electricity access and food security in protracted refugee situations•Access and income partially linked to refugee households' severe food insecurity•Local conditions largely affect refugee households' severe food insecurity.•Female-headed and larger households are more vulnerable to severe food insecurity.